The Speaking Competence of EFL Students at an Indonesian Suburb Vocational School - Muljani, Muljani; Suwartono, Tono (Universitas Muhammadiyah Jember, 2020)
This study aimed to assess speaking ability of the vocational school EFL students. The study involved 108 students of the Accounting Department at a vocational school in the suburban area of Banyumas Regency, Central Java Province, Indonesia. In this study, convenience sampling was used. The data were collected using document of student speaking scores elicited from transactional speaking formative assessments.Â The scores of studentsâ€™ speaking competence in the test were classified to determine their level of competence.The data were analysed using the descriptive statistic and visualized in charts. Therefore, the average, percentage and frequency distribution of the studentsâ€™ scores were obtained. The results have shown that studentsâ€™ speaking ability of 67 students or 62% reached an average of 83.61, falling to category â€œGoodâ€. In addition, there were 6 students or 5,6% who could achieve very good level. Then, there were 34 students or 31,5% who could reach average level. In other words, the technique implemented in the speaking assessment showed good result. Â With regard to the finding, it was recommended that it should be good motivation and challenge for the English teachers to encourage the students to be more confident in speaking English and provide them with more opportunity to practise extensively outside the classroom.